The Impact of Tax Reform, Subjective Norms and Social Norms on SME’s Tax Compliance during the Covid-19 Pandemic - Agustine Dwianika; Putri Dwi Wahyuni; Fachrul Roza (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2023)
This study aims to determine the direction of tax reform, subjective norms and during social norms on SME tax obligations of SMEs in DKI Jakarta Region during Pandemic Covid-19 collected by questionnaires. Result shows partial taxation reforms and social norms have a positive impact on SME tax obligations, but subjective norms are not related to SME tax obligations. In addition, tax reform , subjective norms, and simultaneous social norms are positive for taxpayer compliance. This finding would be useful for DGT for brainstorming references of SME’s policy and tax strategy.